PERBANDINGAN NASKAH SETRA KARESMEN "LUTUNG KASARUNG" KARYA SAYUDI DENGAN NASKAH GENDING KARESMEN "PURBASARI AYUWANGI" KARYA HATO'AN WANGSASENJAYA - Tyas Nastiti Puri, - (2022)
This study discusses about comparison structure of the drama script and the story elements in the setra karesmen "Lutung Kasarung" by Sayudi and gending karesmen "Purbasari Ayuwangi" by Hato'an Wangsasenjaya. The purpose this study was to find out the structure of the drama script, the elements of the story, and to compare the structure and elements of the story in the literary setra karesmen "Lutung Kasarung" and gending karesmen "Purbasari Ayuwangi". The method used is descriptive qualitative method with library research techniques. The theory used to analyze the object of research is using a drama structure approach from several experts, the concept of Robert Stanton's story elements, and the comparative literary method of Sapardi Djoko Damono. Based on the results of the analysis there is a difference between the structure of setra karesmen "Lutung Kasarung" and gending karesmen "Purbasari Ayuwangi". Setra karesmen "Lutung Kasarung" questionnaire consists of four structures, namely prologue, dialogue, scenes, and epilogue. Gending karesmen "Purbasari Ayuwangi" also consists of four structures, namely dialogue, rounds, karamagung, and soliloquy/monologue. The story elements which cover the theme and facts of the story on setra karesmen "Lutung Kasarung" and gending karesmen "Purbasari Ayuwangi" have similarities because they come from the same story. However, setra karesmen "Lutung Kasarung" study document has an element of story that is more complete in terms of flow and characterization. The structure of the drama script and the story elements that have been analyzed are then compared. Based on the results of the comparison, there are many differences between the two texts even though both come from the same story. Keywords: gending karesmén "Purbasari Ayuwangi"; comparasion; story elements; gending karesmén "Purbasari Ayuwangi" structure